2014
DOI: 10.1016/j.bjhh.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell disease and pregnancy: analysis of 34 patients followed at the Regional Blood Center of Ribeirão Preto, Brazil

Abstract: ObjectiveThe objective of this study was to verify the evolution of pregnancies in sickle cell patients followed at one institution over a period of 12 years (January 2000 to June 2012).MethodsThe study evaluated 34 pregnant women with sickle cell disease with a mean age of 23.9 ± 5.3 years. The incidence of obstetric complications, non-obstetric complications linked to sickle cell disease and complications in the newborn were analyzed.ResultsA total of 26% of the cases reported previous miscarriages, 20% had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
27
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 15 publications
11
27
1
5
Order By: Relevance
“…12,19,22,23 Pinto S et al has reported vasoocclusive crisis in 61.7% of pregnant SCD patients and acute chest syndrome as high as 29.4%. 15 However, about 18.05% of vaso occlusive crisis and 5.56% of acute chest syndrome were observed in this study, which is consistent with an observational study in French Guiana where SCD has an incidence of 1 in 235 births. 10 Infective complications observed in this study were mainly urinary tract infections and pneumonia which were controlled without further complications.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…12,19,22,23 Pinto S et al has reported vasoocclusive crisis in 61.7% of pregnant SCD patients and acute chest syndrome as high as 29.4%. 15 However, about 18.05% of vaso occlusive crisis and 5.56% of acute chest syndrome were observed in this study, which is consistent with an observational study in French Guiana where SCD has an incidence of 1 in 235 births. 10 Infective complications observed in this study were mainly urinary tract infections and pneumonia which were controlled without further complications.…”
Section: Discussionsupporting
confidence: 92%
“…9,15 Similar to many other studies, we found that obstetric complications like preeclampsia and gestational hypertension were high in women with sickle cell disease with a higher risk in homozygous (HbSS) genotype. [9][10][11][15][16][17][18][19] Eclampsia which is a life threatening complication of preeclampsia was reported to be 10 times high in HbSS women. 17 This study also showed a higher incidence of eclampsia in consistent with an earlier metaanalysis and also reports from other states of India.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations